Baseline survey of environmental parameters, radiation, and drip water hydrochemistry in Niah Caves (Sarawak, Malaysia) - Mohan Viswanathan, Prasanna; Dodge-Wan, Elisabeth (2024)
Relict caves in fenglin karst may typically have numerous entrances and openings. Hence, they host a variety of environments in which parameters such as light, airflow, humidity, and temperature may vary significantly over short distances. Similarly, drip water hydrochemistry, including isotopic values, may vary due to different contributions of various sources and residence time in the karst. This study investigated environmental parameters, including radiation, using hand-held instruments, along a transect within several major caves in the Niah karst of Sarawak (Malaysia). This has led to a baseline data set which showed an inverse relationship between humidity and temperature, gamma radiation levels that are about 25% of that in surrounding non-karst region, and high percentages of twilight zones in the studied caves. Airflow was found to be variable, with high values of 530 m3/s in Painted Cave and 122 m2/s in parts of Gan Kira passage, with flow towards the southeast at the time of the study. The hydrochemistry of the drip water and surface water was also analyzed and found to be dominantly Ca–Mg–Cl water type which indicates dissolution of minerals through water–rock interaction. In addition, the cave environment, particularly air temperature, humidity, and ventilation, also influences the drip water composition and isotopic values. Three different origins (precipitation, evaporation, and paleo-recharge) of drip water have been identified through the δ18O-δ2H diagram. Enriched isotopic values were observed in the cave entrance due to increased evaporation caused by lower humidity and higher air temperature. Factor analysis identifies the key geochemical processes responsible for the drip water chemistry. The outcome of this study provides the first baseline environmental data for the Niah caves, which could support future initiatives for sustainable management of this famous archeological site in southeast Asia.